Aggressive Export Project. - Ahlberg, Ase; Braddock, Christopher; Dallison, Lyn; Furmark, Anneli; Leonard, Robert; Lieberman, Rhonda; McIllwraith, Janet (Auckland : Pilot (Student Gallery of the Visual Arts Programme (BVA) at Auckland Institute of Technology, New Zealand), 1996)
Iaing, Roby and Melissa ; Ahlberg, Ase ; Jensen, Tatiana ; Mellon, Ryan Drew ; Tomasson, Emil ; Murray, Davina ; Anderson, Barbara ; Kjellgren, Jonas ; Mirabella, Jamie ; Rajakumar, Ravi ; Burton, Caroline ; Furmark, Anneli ; Gustavsson, Patrick
Engels
Aggressive Export Project, Pilot, Auckland, 1 October - 25 October 1996 : New Jersey and Swedish Aggressive Export ; Pilot, Umea, 1 October - 25 October 1996 : New Zealand Aggressive Revenge
boek